Orbital Compartment Syndrome: An Update With Review Of The Literature - McCallum E (Dove Medical Press, 2019)
Ewan McCallum, Shay Keren, Matthew Lapira, Jonathan H Norris Oxford Eye Hospital, John Radcliffe Hospital, Oxford, UKCorrespondence: Jonathan H NorrisOxford Eye Hospital, John Radcliffe Hospital, Oxford, UKEmail jonathan.norris@ouh.nhs.ukAbstract: Orbital compartment syndrome (OCS) is a potentially blinding condition characterized by a rapid increase in intra-orbital pressure. OCS is most commonly seen in the context of intra-orbital hemorrhage secondary to either trauma or surgery. A review of the literature indicates that better visual outcomes are achieved when interventions occur within the first 2 hrs. There are reports of visual recovery after a delay in management and consideration should be given to intervention even when presentation is delayed. Reported interventions include: lateral canthotomy with cantholysis, bony orbital decompression and treatment of the underlying cause.Keywords: orbit, compartment, management, review